Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.6338
|View full text |Cite
|
Sign up to set email alerts
|

SAT0119 Pregnancy outcomes in women with and without rheumatoid arthritis

Abstract: BackgroundPrior studies have suggested higher rates of preterm birth in pregnancies to women with rheumatoid arthritis.ObjectivesWe sought to identify differences in the pregnancy outcomes of women with and without RA, and pregnancies that occurred prior to and following RA diagnosis.MethodsA cross-sectional survey was completed by 75 women with RA age-matched to 75 women without RA. Information collected about each prior pregnancy included: pregnancy outcome (spontaneous abortion, stillbirth, elective termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Rheumatoid arthritis (RA) is known to be an auto-immune disease where the pathogenesis is attributed to the signaling pathways of different cytokines [48][49][50]. In the context of RA associated with pregnancy, Clowse et al [51] reported that women with pregnancies after being diagnosed with RA have higher rates of pregnancy related adverse outcomes such as miscarriage, stillbirth or ectopic pregnancy. Additionally, there are reports suggesting that pro-inflammatory cytokines are a risk factor for EP [52].…”
Section: Immune-response Related Signaling Pathways Are Highly Enrich...mentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is known to be an auto-immune disease where the pathogenesis is attributed to the signaling pathways of different cytokines [48][49][50]. In the context of RA associated with pregnancy, Clowse et al [51] reported that women with pregnancies after being diagnosed with RA have higher rates of pregnancy related adverse outcomes such as miscarriage, stillbirth or ectopic pregnancy. Additionally, there are reports suggesting that pro-inflammatory cytokines are a risk factor for EP [52].…”
Section: Immune-response Related Signaling Pathways Are Highly Enrich...mentioning
confidence: 99%
“…While there are limited data on the incidence of postpartum flares in axSpA, evidence suggests that postpartum disease activity worsens in up to 46% of women with RA or psoriatic arthritis. 27,28 Many women with inflammatory arthritis wish to breastfeed and it is important that they hear from their physicians that most anti-rheumatic medications are considered safe with breastfeeding.…”
Section: Postpartum Flares and Breastfeeding Doctor Megan Clowsementioning
confidence: 99%
“…But even if they were present in breastmilk, bDMARDs will be degraded in the newborn's digestive tract with no chance for absorption (consider that bDMARDs are administered intravenously or subcutaneously, not orally). CTZ was shown to be absent in the breastmilk and breastfed children did not show any particular adverse event [17]. The exposure to immunosuppressive drugs, especially to bDMARDs, during late pregnancy poses the question about the immune competence of the neonate and the approach towards vaccinations.…”
mentioning
confidence: 98%